Thinking outside the framework: equitable research partnerships for environmental research in Australia. - Carter, Jennifer L. (Geographical Journal, 2008)
Many environmental science research programmes now adopt community-based philosophies and designs, although there are few applications in Australian Indigenous communities. This research describes the development and testing of a framework of engagement to guide collaboration between Indigenous and non-Indigenous Australians during an environmental sciences research project. That project aimed to assess trepang (sea cucumber) stocks in Aboriginal waters, and determine the commercial harvest potential of the resource to local people. Its objectives were to undertake trepang survey and mapping, integrate Indigenous knowledge about the resource, and model the existing catch data of commercial fishers operating in the region. The framework of engagement developed to guide the research process comprised a goal, research stages, and a number of guiding principles for collaboration, which were constructed from content analysis of available guidelines and literature and from data gathered during expert interviews. Further data were gathered using participant observation, while implementing the trepang research in accordance with this framework of engagement, and these data were analysed to test and evaluate the framework. Findings indicate discursive and reflective approaches such as action research or adaptive management may better facilitate equitable research partnerships for sustainable development.